Parametric optimum design criteria of a thermophotovoltaic cell. Issue 1 (29th June 2017) - Yang, Zhimin; Wang, Junyi; Chen, Xiaohang; Lin, Guoxing
Abstract : A new model of the thermophotovoltaic cell (TPVC) including internal and external irreversible losses is proposed. Expressions for the efficiency and power output of the TPVC are analytically derived. The curves of the temperatures of the emitter and the photovoltaic (PV) cell, two heat flows of the TPVC, and current density of the PV cell varying with the voltage output are presented through numerical calculation. The effects of the voltage output of the PV cell and the band gap energy of the semiconductor material in the PV cell on the efficiency and power output are discussed in detail. The maximum efficiency and power output density are calculated. The choice criteria of some key parameters are supplied. The influence of the temperature of the heat source on the performance of the TPVC is revealed. The lower and upper bounds of the optimized parameters are determined. The results obtained here may provide some theoretical guidance for the optimal design of practical TPVCs. © 2017 American Institute of Chemical Engineers Environ Prog, 37: 513–517, 2018